Reception and evolution of the idea of eugenics in Polish lands during the 19th and the 20th centuries - Słoniowska, Anna (Studia Ecologiae et Bioethicae, 2012)
Nowadays people confine eugenics to one period (The Second World War), and one place (Nazi Germany). But the truth is that eugenics existed in almost every country, including Poland. In the 19th century, Francis Galton divided the practice of eugenics into positive and negative categories. In Poland, the first of the two had greater popularity, but the negative category had its supporters too. From the beginning, Polish eugenics was associated with the political and social situations in the country. After 123 years of annexation and after The First World War, Poland was threatened by a demographic disaster. The eugenicists tried to solve those problems. Doctor Leon Wernic arose to be the leader of the eugenicists. He was the initiator of many reforms in the +eld of medicine, education, and law. =e eugenicists have established marriage counseling and even insisted upon conscious maternity. However as racist slogans become more frequent in the lead-up to the Second World War, most Polish Eugenicists were opposed to sterilization, castration, and the elimination of people.